2023
DOI: 10.1002/jmv.29309
|View full text |Cite
|
Sign up to set email alerts
|

mRNA‐HPV vaccine encoding E6 and E7 improves therapeutic potential for HPV‐mediated cancers via subcutaneous immunization

Seonghyun Lee,
Hyunho Yoon,
Seol Hee Hong
et al.

Abstract: The E6 and E7 proteins of specific subtypes of human papillomavirus (HPV), including HPV 16 and 18, are highly associated with cervical cancer as they modulate cell cycle regulation. The aim of this study was to investigate the potential antitumor effects of a messenger RNA‐HPV therapeutic vaccine (mHTV) containing nononcogenic E6 and E7 proteins. To achieve this, C57BL/6j mice were injected with the vaccine via both intramuscular and subcutaneous routes, and the resulting effects were evaluated. mHTV immuniza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
(102 reference statements)
0
3
0
Order By: Relevance
“…Different from the ionizable lipid SM-102 in mHTV-02, DLin-MC3-DMA or other similar self-developed ionizable lipids were used in gDE7 (36) and HPV mRNA-LNP (37) targeting HPV16 E7. Although SM-102 delivery system was also chosen in the mHTV vaccine reported by Lee et al (38), the lipid composition was SM-102/6,69-trehalose dioleate/ DOPE/butyl lithocholate/DMG-PEG2000 (molar ratio of 25:25:10: 38.5:1.5). The different properties in LNP-mediated RNA delivery may contribute to distinct features of these vaccines, such as mRNA transfection efficiency, biodistribution, and administration route.…”
Section: Discussionmentioning
confidence: 99%
“…Different from the ionizable lipid SM-102 in mHTV-02, DLin-MC3-DMA or other similar self-developed ionizable lipids were used in gDE7 (36) and HPV mRNA-LNP (37) targeting HPV16 E7. Although SM-102 delivery system was also chosen in the mHTV vaccine reported by Lee et al (38), the lipid composition was SM-102/6,69-trehalose dioleate/ DOPE/butyl lithocholate/DMG-PEG2000 (molar ratio of 25:25:10: 38.5:1.5). The different properties in LNP-mediated RNA delivery may contribute to distinct features of these vaccines, such as mRNA transfection efficiency, biodistribution, and administration route.…”
Section: Discussionmentioning
confidence: 99%
“… 1 For example, a recent study showed that a messenger RNA-HPV therapeutic vaccine (mHTV) exhibited strong immunogenicity and anti-tumor effects in mice and non-human primates, positioning mHTV as a promising therapeutic and prophylactic vaccine for HPV. 98 …”
Section: Classifying Mrna Cancer Vaccinesmentioning
confidence: 99%
“…HPV-16 oncoprotein-expressing vaccines based on DNA [ 12 ], mRNA [ 13 ], viral vectors [ 14 , 15 ], proteins [ 16 ], or other platforms [ 17 ] have shown efficacy in mouse models. Treatment with checkpoint inhibitors such as antibodies to PD-1 or therapeutic vaccines also achieved tumor regression or partial responses in humans with respiratory papillomatosis due to chronic airway infection by HPV-6 or -11 [ 18 ], moderate to advanced cervical intraepithelial neoplasia, and HPV + head and neck cancers [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%